GAMBARAN PENGETAHUAN PENGETAHUAN IMPAKSI GIGI MOLAR KE TIGA DAN TINGKAT KECEMASAN TINDAKAN ODONTEKTOMI (Jurnal Terapi Gigi dan Mulut, 2023)
Good oral health can be realized through knowledge and good and correct behavior towards the maintenance of dental and oral health. Knowledge is a factor that forms erroneous behaviors and attitudes towards maintaining dental and oral health. A person who has never experienced dental care is more likely to arise anxiety. This study aims to analyze the knowledge picture of the impactation of the third molar teeth and the level of anxiety of the odontectomy action. This type of research is a literature study. Data collection based on the study of literature data is then analyzed. The results of the literature analysis study concluded that the third molar dental impaction knowledge was in the moderate category with a percentage of 74.1%. The results of the study on the level of anxiety showed that before odotectomy, they did not experience anxiety with a percentage of 57%. The results of the literature from Pratiwi's research (2021) show that having a level of knowledge either does not experience anxiety or has lower anxiety. So it can be concluded that the higher a person's knowledge, the lower the level of anxiety felt. Supported by the research of Bachri (2017) that the level of knowledge affects the awareness and understanding of stimuli.